Phosphatidylserine Exposure in Thalassemia Β Patients - Sangging, Putu Ristyaning Ayu; Sutyarso, Sutyarso; Busman, Hendri (Medula, 2024)
Thalassemia is a genetic disorder that involves the formation of abnormal hemoglobin. Thalassemia is divided into two main categories namely alpha and beta thalassemia depending on the hemoglobin chain affected. Although some categories of thalassemia are mild and cause only mild anemia and iron deficiency problems in patients, other, more severe forms of thalassemia can result in death. Thalassemia sufferers can get treatment according to the severity of the condition. The degree of ineffective erythropoiesis is known to be associated with clinical severity in individuals with thalassemia. However, the association of ineffective erythropoiesis biomarker levels with different thalassemia genotypes is limited. Studies have explored levels of red blood cells exposed to phosphatidylserine and ineffective erythropoiesis biomarkers in patients with different genotypes. Based on the results of the review, beta thalassemia patients have the highest GDF-15 levels, followed by patients with non-deletal alpha thalassemia. Patients with non-delesional alpha thalassemia showed elevated hemoglobin levels and decreased GDF-15 levels after splenectomy. Patients with beta thalassemia and non-delesional alpha thalassemia had the highest levels of red blood cell exposure to PS and ineffective erythropoiesis biomarkers, which correlated with the clinical severity of thalassemia. Differences in erythropoiesis rates are not effective in thalassemia, which emphasizes the need for different treatment approaches in patients with different thalassemia genotypes.